PENGARUH KREDIT MACET TERHADAP PROFITABILITAS MELALUI KECUKUPAN MODAL, BIAYA DAN PENDAPATAN OPERASIONAL - Akbar, M. Taufik; P., Moeljadi; Djazuli, Atim (Jurnal Bisnis dan Manajemen, 2018)
This study analyzes both of directly effects between NPL on ROA and indirectly effect through CAR and BOPO. As an explanatory study, research framework developed by testing the mediation effect of CAR and BOPO in order to increasing the effect of NPL to ROA. Subjects of this study were all the private bank listed in Indonesia Stock Exchange (IDX). Based on population criteria stated previously the total population was 25 companies. The sampling technique used in this research was census method with total unit data 125 in five year period. By using path analysis with software SPSS 23 version, findings revealed that NPL have no significant effect on both of CAR and ROA. Thus, NPL have negative significant effect on BOPO. Otherwise, CAR and BOPO have positive significant effect to ROA. In testing the mediating effect, BOPO fully mediating in the effect of NPL on ROA, in contrary CAR was not. Discussion and suggest for future research are discussed further in this study.Â DOI :Â https://doi.org/10.26905/jbm.v5i1.2318